2016
DOI: 10.1002/2016wr019003
|View full text |Cite
|
Sign up to set email alerts
|

Reply to comment by Foufoula‐Georgiou et al. on “Climate and agricultural land use change impacts on streamflow in the upper midwestern United States”

Abstract: This reply addresses concerns raised by Foufoula‐Georgiou et al. (2016) on Gupta et al. (2015) through additional regression analysis of streamflow and base flow and with description of the water quality conditions in the Minnesota River prior to European settlements in 1850s.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…The overall influence of agricultural land cover and of changing agricultural practices on streamflows across the Midwest has led to heated debates in recent years [20,[69][70][71][72][73][74][75][76]. In the Upper Mississippi River Basin, LULC has a clear signature on streamflow [77].…”
Section: Agriculturementioning
confidence: 99%
“…The overall influence of agricultural land cover and of changing agricultural practices on streamflows across the Midwest has led to heated debates in recent years [20,[69][70][71][72][73][74][75][76]. In the Upper Mississippi River Basin, LULC has a clear signature on streamflow [77].…”
Section: Agriculturementioning
confidence: 99%
“…Foufoula-Georgiou et al (2015) compared daily hydrographs of the Redwood River in southwestern Minnesota for two similar precipitation years (1971 and 2002) and suggested that increased daily streamflow in 2002 was due to the presence of tile drainage and adoption of soybean in the landscape. However, Foufoula-Georgiou et al (2015) overlooked the role of stored soil water in comparing daily hydrographs between these two years (Gupta et al, 2016e). In further analysis of bi-monthly streamflows, Foufoula-Georgiou et al (2015) concluded that increased streamflow from May-June was primarily due to land use changes (adoption of soybean and tile drainage) because there was not much difference in May-June precipitation distributions before and after adoption of the above LULC changes.…”
mentioning
confidence: 99%